Nghiên cứu hoạt tính chống oxi hóa của vỏ khoai lang trên mỡ lợn. - Vinh, Nguyễn Đắc; Hà, Hoàng Văn; Nga, Hán Thị Phương; Quyên, Vũ Thị; Hương, Trần Thu (Vietnam Journal of Chemistry, 2012)
Sweet potato peel, as a natural antioxidant was evaluated during 43 days storage of lard at 50 and 70oC. Peroxide values and IP200 were used as criteria to assess the antioxidant activity of sweet potato peel extracts. Different organic solvents, including ethanol, ethylacetate, acetone and n-hexane, were used to prepare extracts of sweet potato peels. Composition of lard was analyzed by GC-MS. The main composition of lard was stearic acid (40%), palmitic acid (19.9%), and oleic acid (16.2%). After 43 days storage at 50oC, lard, containing ethanol extract of sweet potato peel, showed the lowest value of peroxide value. After 43 days storage at 70oC, lard, containing 2%, 3%, 4% and 5% of ethanol extracts of sweet potato peel, showed lower values of peroxide value than the control sample and the lard containing 100 ppm of BHA. These results illustrate that the ethanol sweet potato peel extract, at various concentrations, exhibited very strong antioxidant activity which was equal to synthetic antioxidant (BHA). Therefore, the ethanol sweet potato peel extract can be used as a natural antioxidant to suppress lipid oxidation.